The effect of a polyherbal oral formulation in the management of essential hypertension: an open label, pilot clinical study - Sane, Rohit; Dawkhar, Suhas; Ambulkar, Pranit; Mandole, Rahul (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Effective control of blood pressure in patients with hypertension decreases cardiovascular mortality. However, many hypertensives are unresponsive to standard antihypertensive treatment. Research has found anti-hypertensive potential in the Ayurvedic drugs Brahmi (Bacopa monnieri) and Shunthi (Zingiber officinale). Hence, a pilot study was conducted to evaluate the efficacy and safety of Capsule Artyl (the oral formulation of Brahmi and Shunthi) as a treatment option in hypertensive subjects. Methods: There were 30 hypertensive subjects attending out-patient departments of clinics in Maharashtra, India were enrolled in this four-week, open label, single arm study. All subjects received capsule Artyl (500mg) twice a day orally daily. The mean systolic (SBP) and diastolic blood pressure (DBP) on days 1 and 28 of the study were compared along with the mean arterial pressure (MAP). Results: The mean SBP was significantly lesser on day 28 (141.86±12.54mm Hg) as compared to the mean SBP recorded on day 1 (155.48±19.37mm Hg) (p<0.001). The mean DBP on day 28 (89.66±6.8mm Hg) was lesser than that on day 1 (90.34±7.44mm Hg) but this difference was not statistically significant (p>0.05). There was a significant decrease in the mean value of MAP on day 28 (107.06±7.03mm Hg) as compared to that on day 1 (112.06±10.75mm Hg) (p<0.01). Conclusions: Capsule Artyl significantly decreased the BP in hypertensive patients, without any adverse effects. Controlled trials are needed to confirm the positive outcome of this promising herbal formulation in hypertensive patients.